Nutrition-Based Strategies to Reduce Exercise-Induced Muscle Damage and Soreness - Barnes M (MDPI (Basel, Switzerland), 2023)
Exercise induced-muscle damage (EIMD) occurs after strenuous and/or novel exercise that involves repeated eccentric contractions [...].
Keywords: Humans; Muscle, Skeletal; Pain; Exercise; Muscle Contraction